Microextrusion-Based 3D Printing for Mesoscale Interfacial Structural Designing in Anode-Supported Solid Oxide Fuel Cells - Seo, Haewon (2024 IEEE 19TH INTERNATIONAL CONFERENCE ON NANO/MICRO ENGINEERED AND MOLECULAR SYSTEMS, NEMS 2024, 2024)
Solid oxide fuel cells (SOFCs) are attracting considerable interest as promising electrochemical devices due to their unparalleled energy conversion efficiency. Nevertheless, they still encounter various challenges, particularly associated with cost competitiveness in the energy market. This paper reports an innovative structural modification of the electrode-electrolyte interface in anode-supported SOFCs on the mesoscale order (10-100 mu m) by microextrusion-based 3D printing coupled with temperature control to enhance the volumetric power density of individual cells. Moreover, the mechanism whereby the mesostructural modification improves the electrochemical performance of SOFCs is elucidated by two-dimensional (2D) numerical simulation.